INTEGRASI KARAKTER DISIPLIN DAN TANGGUNG JAWAB PADA PELAJARAN SENI BUDAYA DI MI AL ISLAM YOGYAKARTA - Jonata Jonata; Muqowim Muqowim (Borneo : Journal of Islamic Studies, 2021)
Education is very important for the Indonesian generation, especially at the lowest level, namely TK and MI/SD. One of them is at Madrasah Ibtidaiyah Al Islam Yogyakarta, because of the low character of this school, therefore it will integrate SBdP subjects in the learning process. Meanwhile, SBdP subjects are not only seen as theory but have reciprocity. students to be good and have noble character. The aim is to instill the character of discipline and responsibility at Madrasah Ibtidaiyah Al Islam Yogyakarta. This research uses qualitative research. The results of the first research are planting and growing character in students both in theory and practice. Both students and teachers can implement the integration of discipline and responsibility through extracurricular activities in batik, dancing, and so on. The three students can integrate learning media in instilling their character.